ANALISIS PENGARUH RETURN ON INVESTMENT, FIXED ASSETS RATIO, FIRM SIZE, RATE OF GROWTH DAN ASSETS STRUCTURE TERHADAP DEBT TO EQUITY RATIO PADA PERUSAHAAN MANUFAKTUR YANG TERCATAT DI BURSA EFEK INDONESIA PERIODE 2008-2010 - Andy Soebagyo, 10.42.02.0127 (Students Journal of Economic and Management, 2013)
This study aims to examine and describe the influence of return on investment, fixed assets ratio, firm size, rate of growth and asset structure of the debt to equity ratio at manufacturing companies listed on the Indonesia Stock Exchange. Research technique used was purposive sampling method. Classical assumption of normality and testing, Regression Analysis, Hypothesis Testing with the T-test, Hypothesis test with F test danUji coefficient of determination. The analysis and discussion of this study indicate that the return on Investment has a negative effect on the debt to equity ratio is acceptable. fixed assets ratio is shown to be positively related to variable debt to equity ratio. variable rate of growth and no significant positive effect on variable debt to equity ratio assets structure has positive and significant impact on variable debt to equity ratio and simultaneous testing in mind that the variable return on Investment, fixed assets ratio, firm size, rate of growth and assets structure significant effect on the debt to equity ratio at Manufacturing Company Go Public in Indonesia Stock Exchange Period 2008 - 2010 Keywords: Return On Investment, Fixedassets Ratio, Firm Size, Rate Of Growth, Assets Structure andÂ Â  Debt To Equity Ratio